Conferment on the degree of Doctor of Philosophy in Finance - Caloia, Angelo (Animo Repository, 1997)
De La Salle University conferred the degree of Doctor of Philosophy in Finance, honoris causa, on Angelo Caloia, member of the Board of Directors of Cassa di Risparmio delle Provinci Lombarde, the biggest savings bank in the world on this date.